A Polystyrene Photoresin for Direct Lithography of Microfluidic Chips. Issue 10 (27th April 2022) - Franco Corredor, Santiago; Mayoussi, Fadoua; Luitz, Manuel; Kick, Andrea; Goralczyk, Andreas; Böcherer, David; Vera, Grace; Helmer, Dorothea; Kotz‐Helmer, Frederik; Rapp, Bastian E.
Abstract: Polystyrene (PS) is the material of choice for many medical, biological, and biomedical applications given its advantageous properties such as high biocompatibility, optical transparency, and the possibility to shape PS using high‐throughput manufacturing methods at low production costs. Due to its properties, PS is an interesting material for the fabrication of microfluidic systems. In microfluidics, rapid prototyping is of high importance for testing new chip layouts and designs during the product development with the aim of significantly accelerating the manufacturing. To allow transitioning and thus significantly faster translation from research to scalable manufacturing, it would be ideal if the same material could be used throughout the whole design pipeline. However, rapid prototyping and high‐resolution shaping of PS, especially on the micron scale, is still limited. In this work, a novel photocurable polystyrene photoresin, is presented which can be shaped using direct optical lithography. Using this PS photoresin, microfluidic chips with feature sizes down to 50 µm and a high optical transparency can be fabricated. The cured PS photoresin shows comparable surface and material properties to commercial PS. This method will enable researchers in the medical, biological and biomedical fields to produce suitable PS structures with commercial equipment. Abstract : Polystyrene (PS) is a material of high importance in the medical, biological, and biomedical fields due to its properties like high biocompatibility, optical transparency, and the capability to shape using high‐throughput manufacturing at low production costs. A photocurable PS photoresin is presented that can be structured using direct lithography methods. PS microfluidic chips can be manufactured within 20 min.